2022
DOI: 10.3390/ma15031244
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Drotaverine Hydrochloride with Ibuprofen and Ketoprofen Nonsteroidal Anti-Inflammatory Drugs Mixtures

Abstract: Formulations with two or more active pharmaceutical ingredients (APIs) are a researched trend due to their convenient use compared with multiple medications. Moreover, drug-drug combinations may have a synergistic effect. Drotaverine hydrochloride (D-HCl) is commonly used for its antispasmodic action. The combination of a spasmolytic and an analgesic drug such as ibuprofen (Ibu) or ketoprofen (Ket) could become the answer for the treatment of localized pain. D-HCl:Ibu and D-HCl:Ket drug-drug interactions leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Leitner et al 24 studied SLE in three binary systems containing paracetamol, with phenylephrine hydrochloride, tramadol hydrochloride, and ibuprofen, respectively. Soare et al 25 reported SLE data for the binary systems of ibuprofendrotaverine hydrochloride and ketoprofen-drotaverine hydrochloride. Zemańkováet al 26 experimentally determined the SLE of four binary systems, including naproxen-indomethacin, naproxen-ibuprofen, naproxen-probucol, and indomethacinparacetamol.…”
Section: Introductionmentioning
confidence: 99%
“…Leitner et al 24 studied SLE in three binary systems containing paracetamol, with phenylephrine hydrochloride, tramadol hydrochloride, and ibuprofen, respectively. Soare et al 25 reported SLE data for the binary systems of ibuprofendrotaverine hydrochloride and ketoprofen-drotaverine hydrochloride. Zemańkováet al 26 experimentally determined the SLE of four binary systems, including naproxen-indomethacin, naproxen-ibuprofen, naproxen-probucol, and indomethacinparacetamol.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, drotaverine can suppress spasm-associated pain and is successfully used in the symptomatic treatment of various conditions such as gastrointestinal, urinary, biliary, vasomotor diseases associated with smooth muscle spasms [1,11], it has a cytostatic effect [12] and improves cognitive function [13]. It is available without prescription in many countries of Central and Eastern Europe (Poland [11,[14][15][16], Hungary [17], Estonia, Croatia, Latvia [4], Romania [18,19]), Africa (Nigeria [20]) and Asia (India [21][22][23], Russia [24], China [25] under several brand names.…”
Section: Introductionmentioning
confidence: 99%
“…The spasmolytic activity of this drug act by inhibiting the phosphodiesterase-4. It shows clinical importance in various disease associated with smooth muscle spam [1][2][3] . The phenylacetic acid derivative, Diclofenac Potasium (DICLO) is classified as a non-steroidal anti-inflammatory medication acts by inhibiting cyclooxygenase enzyme, which is the key enzyme responsible for the synthesis of prostaglandins (PGs).…”
Section: Introductionmentioning
confidence: 99%